Wash and wipe to win over COVID-19 - Saha Susmita; Prachi Saffar Aneja; Bansal Savita; Vibhash Kumar Vaidya; Kumar Paras (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: The COVID-19 is a serious issue in every corner of the globe affecting frontline warriors and other individuals. Appropriate hand hygiene measures are considered to be the most basic but effective steps to control this disease. The objective of the study was to assess the knowledge, awareness, and proper practice of hand hygiene among university undergraduate medical and nonmedical students. Materials and Methods: The present cross-sectional survey was conducted on 703 university undergraduate medical students (MBBS, BDS, BPT, nursing, and allied) and nonmedical students (engineering, law, commerce, etc.) at Shree Guru Gobind Singh Tricentenary University, Gurugram, Haryana, through the Google Forms by a prevalidated questionnaire to assess the knowledge and attitude regarding hand hygiene practices in this COVID-19 pandemic era. Results: The correct responses for questions based on recommended time of handwash (29.7%), minimum time required for alcohol-based hand rub to kill germs (70.1%), recommended concentration of hand rub (50.5%), and effective method of handwash (38.8%) were observed. Only 73% of the medical students and 58% of the nonmedical students knew exact steps of handwashing (as per the World Health Organization guidelines). Ninety-one percent of all the respondents agreed that they became more conscious about hand hygiene during COVID-19 pandemic. Eighty-two percent of the participants opined that the steps of hand hygiene must be included in routine curriculum. Conclusions: The results of the current survey presented an average score regarding hand hygiene knowledge and practices among university students for both medical and nonmedical streams in this COVID-19 pandemic era.